2009
DOI: 10.1073/pnas.0908238106
|View full text |Cite
|
Sign up to set email alerts
|

Performance level modulates adult age differences in brain activation during spatial working memory

Abstract: Working memory (WM) shows pronounced age-related decline. Functional magnetic resonance imaging (fMRI) studies have revealed age differences in task-related brain activation. Evidence based primarily on episodic memory studies suggests that brain activation patterns can be modulated by task difficulty in both younger and older adults. In most fMRI aging studies on WM, however, performance level has not been considered, so that age differences in activation patterns are confounded with age differences in perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
166
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(215 citation statements)
references
References 55 publications
39
166
2
Order By: Relevance
“…Evidence for the behavioral relevance of this finding was generated by a whole-brain analysis, which showed that in both younger and older adults, MFG-PPA connectivity in delay 2 correlated with subsequent WM accuracy (both P < 0.05, corrected for multiple comparisons) (4). These findings suggest that those participants who were best able to reactivate the stored memoranda postinterruption (via restoration of MFG-PPA connectivity) performed with the highest WM accuracy, highlighting the importance of assessing individual differences even in age-comparative studies (21). However, as a group, older participants were unable to attain levels achieved by the younger participants, which suggests an age-related reactivation deficit (support for hypothesis 2).…”
Section: Resultsmentioning
confidence: 59%
“…Evidence for the behavioral relevance of this finding was generated by a whole-brain analysis, which showed that in both younger and older adults, MFG-PPA connectivity in delay 2 correlated with subsequent WM accuracy (both P < 0.05, corrected for multiple comparisons) (4). These findings suggest that those participants who were best able to reactivate the stored memoranda postinterruption (via restoration of MFG-PPA connectivity) performed with the highest WM accuracy, highlighting the importance of assessing individual differences even in age-comparative studies (21). However, as a group, older participants were unable to attain levels achieved by the younger participants, which suggests an age-related reactivation deficit (support for hypothesis 2).…”
Section: Resultsmentioning
confidence: 59%
“…This indicates that HC-DLPFC coupling may be a systems-level correlate specific to spatial WM performance that can be found in several species. Impaired information processing during WM has been found to be a core cognitive deficit in schizophrenia (Barch and Ceaser, 2012) and has also been observed during normal aging (Nagel et al, 2009). Virtual navigation paradigms have already been successfully used in aged subjects and in clinical populations (Konishi et al, 2013;Sneider et al, 2013;Spieker et al, 2012;Yuan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This prediction is supported by the results from human lesion studies showing that frontal lesions have weak or no negative effects on simple workingmemory maintenance (e.g., Volle et al 2008;Barbey et al 2013). In contrast, frontal lesions, notably in the dorsolateral cortex, have marked impact on working-memory manipulation operations, and functional imaging studies have shown elevated dorsolateral prefrontal activity as a function of the complexity of workingmemory operations (e.g., Nagel et al 2009;Nyberg et al 2009b). It should be stressed that increased complexity can be instantiated by using tasks that require that some operation is performed on the information that is maintained in working memory (e.g., letter-number sequencing or digit-span backward) or by increasing the number of items that have to be maintained (as in Sternberg type of tasks).…”
Section: How Can Information In Working Memory Be Manipulated and Updmentioning
confidence: 99%